Inventory system for FCSIT / Jayakumar Kunju - Jayakumar, Kunju (2003)
This e-inventory system is an Internet based system developed. As a web based application, e-inventory system's client works in tandem with the server, operating over the internet. The server side contains all the related operating applications, and data storage. Web browser is involved to retrieve information from the web server. It is a centralized kiosk for the retrieval and collection of information.There are many example or current inventory system either is online or stand-alone system that have been referred during the system design. Furthermore, system functional requirements of this project include login function, output displaying function, search fun functions ads, edit or delete function, output displaying function and user manual. Next, the data flow diagrams is used to illustrate data sources, destinations, flows, store, and transformation of the system. The Online system consist of a few separate module, this include system user architecture design module, authentications module, user management module and product transaction module. For the system development, Windows 2000 will be used as application platform, Microsoft Access server as the database server ASP and ASP. Net as the web page technology, JavaScript and VB Scripts as the scripting language and the IIS as the web server. Moreover, the waterfall model with prototype is the selected methodology to develop the e-inventory system.